Amotl1 mediates sequestration of the Hippo effector Yap1 downstream of Fat4 to restrict heart growth - Chiara V. Ragni (Nature Portfolio, 2017)
Growth of the mammalian heart is controlled by Hippo signalling but how this is regulated is unclear. Here, the authors show that Fat4 (an atypical cadherin) acts upstream of Hippo signalling and Fat4 mutant mice have thicker myocardium, which is mediated by the scaffold Amot1 and transcription factor Yap1.